THE LEARNING TOOLS BASED ON THE REMAP TMPS MODEL (READING CONCEPT MAP TIMED PAIR SHARE) AND THE EFFECTIVENESS OF STUDENTS CRITICAL THINKING SKILLS - Sariah Sariah; Jamaluddin Jamaluddin; Dadi Setiadi (Jurnal Penelitian Pendidikan IPA, 2018)
This study aims to improve critical thinking skills through the application of science-based learning tools REMAP TMPS model ( Reading Concept Map Timed Pair Share ). The type of research was quasi experiment with One Group Pretest-Postest design . The population in this study were all students of class VII at SMPN 4 Pujut and SMPN 6 Pujut with sampling using purpusive sampling technique so that the samples taken are class VII-A at SMPN 4 Pujut and VII-B in SMPN 6 Pujut. instruments used to measure critical thinking skills in the form of answer-question as much as 10. The results showed the average N-gain class VII-A higher than class VII-B. This suggests that REMAP TMPS-based science learning tools has effective toword student critical thinking skills.